Cutaneous Breast Radiation-associated Angiosarcoma: Anterior Chest Wall Reconstruction Options Following Extra-radical Resection. Issue 9 (September 2018) - Mella, Juan R.; Ross, Kimberly M.; Li, George Z.; Pomahac, Bohdan; Raut, Chandrajit P.; Orgill, Dennis P.
Abstract : Background: Radiation-associated angiosarcoma (RAAS) of the breast is a rare complication following breast irradiation with high rates of recurrence and death. To improve survival, we have advocated for an extra-radical resection where the entire irradiated skin and subcutaneous tissue is excised. This results in very large chest defects for which we describe our reconstructive experience. Methods: We performed a retrospective review of patients diagnosed with RAAS and treated with extra-radical resection followed by immediate reconstruction between 1999 and 2017. We analyzed reconstructive options, complications rates, length of stay, and operative times. Results: Extra-radical resections were performed in 35 patients. We reconstructed these large defects with abdominal advancement flaps with split-thickness skin grafting in 25 patients and added a pedicled latissimus dorsi or omental flap in the 10 other patients. Skin grafts took well over the irradiated pectoralis major muscle with a median take rate of over 90%. Average operative times were 150 minutes for those treated with an abdominal advancement flap and skin grafting with a median length of stay of 5 days for all patients. Conclusion: Large anterior chest soft-tissue defects caused by extra-radical resections leaves defects too large to be covered by traditional breast reconstruction flaps. Abdominal advancement, latissimus dorsi muscle, and omental flaps along with skin grafts can be safely performed while leaving other traditional options open for future breast reconstruction. Abstract : Supplemental Digital Content is available in the text.